2009
DOI: 10.1111/j.1472-765x.2009.02630.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing relative release kinetics of faecal indicator organisms from different faecal matrices

Abstract: IMPF: 01.64 RONO: 2480 6260A laboratory assay for comparative characterization of various faecal matrices with respect to faecal indicator organism (FIO) release using artificial rain water. Fresh sheep and beef-cattle faeces, dairy cattle slurry and beef cattle farm yard manure (FYM) were collected from commercial units in south-west England and applied to 20 randomized 1 m2 plots established on permanent grassland. Representative samples from each faecal matrix (n=5) were collected on four occasions over 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
4
39
0
Order By: Relevance
“…The observed E. coli and enterococci densities were comparable to many previously reported values which suggested 10 5 -10 8 fecal organisms per gram of animal waste (Arthurs et al 2001;Diez-Gonzalez et al 2000;Duriez and Topp 2007;Haack and Andrews 2000;Hodgson et al 2009;Meals and Braun 2006;Reddy et al 1981;Sinton et al 2007). The review of Reddy et al (1981) estimated that the average density of fecal coliform was within the range of 10 5 -10 8 /g.…”
Section: Average Concentrations Of E Coli and Enterococci In Manuresupporting
confidence: 89%
See 1 more Smart Citation
“…The observed E. coli and enterococci densities were comparable to many previously reported values which suggested 10 5 -10 8 fecal organisms per gram of animal waste (Arthurs et al 2001;Diez-Gonzalez et al 2000;Duriez and Topp 2007;Haack and Andrews 2000;Hodgson et al 2009;Meals and Braun 2006;Reddy et al 1981;Sinton et al 2007). The review of Reddy et al (1981) estimated that the average density of fecal coliform was within the range of 10 5 -10 8 /g.…”
Section: Average Concentrations Of E Coli and Enterococci In Manuresupporting
confidence: 89%
“…The bars represent standard deviation of triplicate samples of antibiotic-resistant E. coli and enterococci. Experimental evidence suggested that bacteria such as E. coli and enterococci are readily leachable from manure, and improper management of manure could thus lead to contamination of surface and ground waters which are used for water supply, irrigation, and recreational purposes (Anderson and Sobsey 2006;Hodgson et al 2009;Sapkota et al 2007). …”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Modelling of runoff and stormwater contamination is a welldocumented research activity (e.g., (Bhattarai et al, 2011;Burian et al, 2001;Kara et al, 2012;Liu, 1994;L opez-Vicente et al, 2014;Luna et al, 2006;May and Sivakumar, 2009;Vezzaro and Mikkelsen, 2012;Vezzaro et al, 2014;Whelan et al, 2014)) Prior studies of pathogen and indicator mobilisation via overland flow from land applied manures have explored the influence that numerous factors have on mobilisation (Cardoso et al, 2012;Ferguson et al, 2007;Muirhead et al, 2006;Stout et al, 2005). Those factors include manure type and method of land application (e.g., Hodgson et al, 2009;Miller and Beasley, 2008;Ramirez et al, 2009;Saini et al, 2003;Thurston-Enriquez et al, 2005), slope and ground cover (e.g., Cardoso et al, 2012;Davies et al, 2004;Ferguson et al, 2007;Hodgson et al, 2009;Miller and Beasley, 2008;Stout et al, 2005;Thurston-Enriquez et al, 2005;Trask et al, 2004;Winkworth et al, 2008;Yeghiazarian et al, 2004), rainfall intensity and antecedent soil moisture (Bradford and Schijven, 2002;Davies et al, 2004;Ramirez et al, 2009;Saini et al, 2003;Schijven et al, 2004;Sistani et al, 2009;Yeghiazarian et al, 2004), and chemical properties (e.g., …”
Section: Introductionmentioning
confidence: 99%
“…Those factors include manure type and method of land application (e.g., Hodgson et al, 2009;Miller and Beasley, 2008;Ramirez et al, 2009;Saini et al, 2003;Thurston-Enriquez et al, 2005), slope and ground cover (e.g., Cardoso et al, 2012;Davies et al, 2004;Ferguson et al, 2007;Hodgson et al, 2009;Miller and Beasley, 2008;Stout et al, 2005;Thurston-Enriquez et al, 2005;Trask et al, 2004;Winkworth et al, 2008;Yeghiazarian et al, 2004), rainfall intensity and antecedent soil moisture (Bradford and Schijven, 2002;Davies et al, 2004;Ramirez et al, 2009;Saini et al, 2003;Schijven et al, 2004;Sistani et al, 2009;Yeghiazarian et al, 2004), and chemical properties (e.g., Bradford and Schijven, 2002;Davies et al, 2004). Not surprisingly, mobilisation fractions (i.e., proportion of organisms in land-applied manures that are mobilised during a rain event) reported in the literature vary widely (Hodgson et al, 2009;Stout et al, 2005;Trask et al, 2004). Hence, rather than exploring all the conditions and factors described above, we conducted a series of pilot-scale experiments to characterize mobilisation of indicator organism and zoonotic pathogens from an intense rainfall event for one pasture condition.…”
Section: Introductionmentioning
confidence: 99%
“…The notable difference recorded during summer 2012 that might help explain the lack of observed regrowth was the amount (and patterns of distribution) of daily rainfall. This was far higher than that experienced in 2013 and most likely led to the detachment of organic material and associated cells from the faecal pats through processes of raindrop impact and subsequent mobilisation and wash-out of E. coli from the faeces into the surrounding environment1127.…”
Section: Discussionmentioning
confidence: 89%